2017
DOI: 10.1002/2016jd026065
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of evapotranspiration estimates based on the surface water balance, modified Penman‐Monteith model, and reanalysis data sets for continental China

Abstract: Evapotranspiration (ET) combines the land‐atmosphere water, energy, and carbon cycles and plays a critical role in climate studies. However, ET is difficult to quantify accurately. This study compares three 1982–2013 ET data sets for China based on surface water balance values, a modified Penman‐Monteith (MPM) model and reanalysis data. Water balance ET data, which have been widely used as benchmark data for regional ET, were calculated with and without considering reservoir water storage. MPM ET values were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 107 publications
(170 reference statements)
2
38
2
Order By: Relevance
“…In terms of the variations of country‐averaged annual ET a over last three decades, we found contrasting trends between pre‐late and post‐late 1990s. This is consistent with the conclusion of Mao and Wang (), which employed a modified Penman‐Monteith model driven by forcing of 2,479 weather stations across China.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In terms of the variations of country‐averaged annual ET a over last three decades, we found contrasting trends between pre‐late and post‐late 1990s. This is consistent with the conclusion of Mao and Wang (), which employed a modified Penman‐Monteith model driven by forcing of 2,479 weather stations across China.…”
Section: Discussionsupporting
confidence: 91%
“…While a wide range of studies have investigated the spatiotemporal pattern of ET a across China (Chen et al, ; Gao et al, ; Li, Liang, et al, ; Mao & Wang, ; Su et al, ; Sun et al, ; Yang et al, ), there exist considerable inconsistencies for both magnitudes and trends of ET a due primarily to the uncertainties in parameters and/or forcing of different models. In the present study, by fully taking advantage of the recent improvements in the nonlinear CR model formulation, we aim to (1) develop a 31‐year (1982–2012), 0.1° ET a product across China, along with independent validations using plot‐scale EC measurements and basin‐scale water‐balance‐derived evapotranspiration rates; (2) determine whether this new CR‐based ET a product improves upon previously available ET a products; and (3) quantify the spatial and temporal variability of ET a in China during the past three decades.…”
Section: Introductionmentioning
confidence: 99%
“…The other two ET data sets were from the Global Land Data Assimilation System (GLDAS), versions 2.0 and 2.1 (Rodell et al, ), which employed the Noah land surface model at a 0.25° spatial resolution. To date, ET is still particularly difficult to measure and simulate, especially at large spatial scales (Mao & Wang, ). Long et al () reported that the North American Land Data Assimilation System (NLDAS) ET , which is basically estimated by land surface models, has the lowest uncertainty compared with the ET results derived from remote sensing and GRACE satellites.…”
Section: Study Site and Datamentioning
confidence: 99%
“…Su, Feng, and Feng (), Su, Feng, Zhou, et al () used reanalyses to examine AE variability over China with respect to climate change and found that the relationship between AE and pan evaporation was complementary with water control and proportional to energy control. Mao and Wang () compared three evapotranspiration data sets for China based on surface water balance values, a modified Penman‐Monteith (MPM) model, and reanalysis data and concluded that reanalysis evapotranspiration variables are consistent with MPM estimates in terms of spatial patterns, interannual variability, and temporal trends at the station scale.…”
Section: Introductionmentioning
confidence: 98%